2020
DOI: 10.1186/s10194-020-01164-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered hypothalamic functional connectivity in post-traumatic headache after mild traumatic brain injury

Abstract: Background Post-traumatic headache (PTH) is one of the most frequent symptoms following mild traumatic brain injury (mTBI). Neuroimaging studies implicate hypothalamic function connectivity (FC) disruption as an important factor in pain disorders. However, it is unknown whether there are alterations in the hypothalamus-based resting state FC within PTH following mTBI at the acute stage and its relationship with headache symptom measurement. Methods Forty-four mTBI patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Our study's finding that VMHC was increased in this area might be explained by enhanced interhemispheric coordination between the bilateral middle frontal gyrus, which might strengthen the capacity of an individual's cognitiveevaluative modulation of unpleasant menstrual pain. In agreement with this, reports have shown that the middle frontal gyrus is related to the cognitive evaluation and modulation of pain in post-traumatic headache (30) and chronic lower back-related leg pain (19).…”
Section: Increased Vmhc and Fc In The Cognitive-evaluative Dimension ...supporting
confidence: 79%
“…Our study's finding that VMHC was increased in this area might be explained by enhanced interhemispheric coordination between the bilateral middle frontal gyrus, which might strengthen the capacity of an individual's cognitiveevaluative modulation of unpleasant menstrual pain. In agreement with this, reports have shown that the middle frontal gyrus is related to the cognitive evaluation and modulation of pain in post-traumatic headache (30) and chronic lower back-related leg pain (19).…”
Section: Increased Vmhc and Fc In The Cognitive-evaluative Dimension ...supporting
confidence: 79%
“…[ 15 ] For example, headache frequency and headache intensity related with hypothalamic functional disconnections in mTBI with post-traumatic headache. [ 16 ] As a special type of traumatic brain injury, DAI patients may have extensive axonal injury that also involves the hypothalamic functional connectivity (FC) pathways and causes associated cognitive and behavioral symptoms. Increasing numbers of DAI studies have found disrupted regional, long-distance, and even network connectivity in patients with DAI.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2021) in a study on patients with mTBI showed an alteration of rs-fMRI measures in the cerebellum and temporal lobe regions and suggested that the FC abnormality is consistent with sensory perception, movement control, and micro-motor coordination in patients after injury. Also, it has been shown that motor network functional activation and connectivity in mTBI patients 10.3389/fnins.2022.1099560 with post-traumatic headache is related to patients' response to avoid movement during pain since physical movement may worsen the pain (Lu et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%